Keren Cytter - A-Z life coaching - Droschl, Sandro 1970- (Sternberg Press, 2016)
An incomplete guide for life. Each person written about is represented by a letter, and when an object turns into a subject it is marked in bold. The form of life coaching described in this book won’t lead the reader to social recognition or financial success. If one of the two occurs after reading this text, it is a coincidence. This book aims to expose the owners of an innocent heart to reality’s true structures and to utilize them for spiritual growth so their soul and body evaporate into the abstract. This book was written from the middle. The contents of these pages have been modified numerous times. Notes were taken, ideas were rewritten—the ones that survived bare the most essential guidelines and wisdom for life.
Keywords: Tsịter, Ḳeren -- 1977-; Ausstellungskatalog -- Künstlerhaus Graz -- 11.06.2016-08.09.2016 -- Graz; Künstlerbuch